Políticas públicas de formação continuada de professores no Brasil: um estudo de caso na rede escolar pública estadual de educação do Paraná e do Rio Grande do Sul - Casagrande, Ieda Maria Kleinert (2015)
This thesis is part of the Research Line Public Policy and School Practice of the Graduate Program in Education of the Federal University of Santa Maria. It is a multiple case study that aimed to identify, interpret and understand the organization of continuous training of public school teachers policies of high school in the cities of Cascavel \ PR and Santa Maria \ RS. In seeking the context of these practices analyzes focused on the Educational Development Program Paraná \ PDE / PR and continuing training policies for teachers resulting from the Proposed Restructuring Curriculum of Secondary Education of the State Secretariat of Rio Grande do Sul Education (SEDUC / RS). The analysis left of the relationship between changes in the workplace that show in different professional sectors, continuing education as a requirement to meet the needs of society governed by the intellectualization of the productive, social and cultural space. In education, continuing education of teachers has been put as essential for professional advancement, this because the decentralized education policy, due to the new organization of the now relaxed and collective work, put on the teacher responsible for the training subjects capable of understanding and enter critically in society. For the development of research used the case study (Yin, 2010; GIL, 2009) and as techniques for data collection semi-structured interviews (CHIZZOTTI, 2012; FLICK, 2009) with teachers and students of state schools as well as analysis technical and official documents of states and schools, laws, plans, courses and continuing education programs sponsored by the Secretaries of State for Education and schools. The main thesis that the proposals for continuing education practice teachers in the public education state networks are consolidating School policies in accordance with the proposals of each State has been confirmed, although in practical terms showed detachment of teachers and students of specific training in the perspective of integrated and polytechnic education. The study made it clear that the inclusion of continuing education programs for teachers contributes to the expansion of production experience and theoretical and methodological knowledge in the subjects that act; He highlighted the contradictions of scientific development that separates science from the workplace and the importance of enhancing teachers' knowledge about the principles underlying the proposed curriculum that takes work, culture, science and technology.